On Conception of Personal Expression - Suslavičius, Antanas (Problemos, 1985)
The dynamics of social behaviour is discussed. Social needs such as that of personal expression, or that of personal contact and others are said to make the beginning of any social act. Further the conditions under which these social needs can be satisfied are considered. A special attention is paid to the evaluation of social act of a person by other persons. The evaluation is examined as support of social conduct. A kind of support is dependent upon the type of personal contact. It is reciprocal one in the social behaviour of ‘collaboration’. Reciprocity is not present in the situation of conflict or of competition. Then a personality does have problems when adapting himself to the situation.